2013
DOI: 10.7763/ijtef.2013.v4.256
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effects of World Oil Price Change on Economic Growth and Energy Demand in Malaysia: An ARDL Bound Testing Approach

Abstract: Abstract-This paper investigates the effects of world oil price change on economic growth and energy demand in Malaysia by using an ARDL bounds testing co-integration approach. The results revealed that changes in world oil price benefitted the Malaysia's real GDP in the short term. Interestingly, the estimated results showed that energy demand is found to be an oil price inelastic and income elastic of demand, consistently in the short and long run. In addition to that, there was a bidirectional causality eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Test outcomes demonstrated that oil prices just influenced economic growth in China and Japan. Yussof and Latif (2013) inspected the impact of oil prices on economic growth in Malaysia utilizing information that stretched out from 1966 to 2006. The autoregressive distributed lag (ARDL) model was utilized to test these impacts.…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Test outcomes demonstrated that oil prices just influenced economic growth in China and Japan. Yussof and Latif (2013) inspected the impact of oil prices on economic growth in Malaysia utilizing information that stretched out from 1966 to 2006. The autoregressive distributed lag (ARDL) model was utilized to test these impacts.…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Test results showed that oil prices only affected economic growth in China and Japan. Yussof and Latif (2013) examined the effect of oil prices on economic growth in Malaysia using data that extended from 1966 to 2006. The ARDL model was used to test these effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…the findings ofMendosa and Vera (2010), Jiménez-Rodríguez and Sánchez (2004),Chai et al (2015),Yussof and Latif (2013),Maheu et al (2018),Hanabusa (2009), Besso and Pamen (2017),Ftiti et al (2016),Malik (2010) Yoshino and Taghizadeh-Hesary (2014),Mhamad and Saeed (2016),Qianqian (2011 ),Gummi et al …”
mentioning
confidence: 91%
“…Moreover, they have found strong evidence that confirm the linearity of the relationship between CP changes and GDP growth. Nonetheless, in recent studies, Yusoff and Latif () have examined the effects of World CP changes on Malaysian economic growth and find that World CP changes positively affect real GDP in the short run. Ibrahim and Said (), however, have found evidence that in the long run the CP and real GDP are cointegrated only through the aggregate CPI and food prices.…”
Section: Introductionmentioning
confidence: 99%